Integrated methodologies of economics and socio-economics assessments in ocean renewable energy: Private and public perspectives. (September 2016) - Dalton, Gordon; Allan, Grant; Beaumont, Nicola; Georgakaki, Aliki; Hacking, Nick; Hooper, Tara; Kerr, Sandy; O'Hagan, Anne Marie; Reilly, Kieran; Ricci, Pierpaolo; Sheng, Wanan; Stallard, Tim
Abstract: This paper offers a holistic approach to the evaluation of an ocean renewable energy (ORE) technology type or specific project in order to provide a comprehensive assessment of both narrow economic and broader socio-economic performance. This assessment incorporates methods from three pillars areas: Economic – financial returns and efficient use of resources, Social – employment, social and community cohesion and identity, and Environmental – including the physical environment and pollution. These three pillars are then considered in the broader context of governance. In order to structure this evaluation, a novel parameter space model was created, defined by the three pillars and by the scale of the system under assessment. The scale of the system ranged from individual components of an ORE project; to projects comprising of a number of devices; through to a geographic regions in which multiple farms may be deployed. The parameter space consists of an inner circle representing the boundary of interest for a private investor, or a firm, developing an ORE project. The outer circle is characterised by assessment tools typically employed at the broader stakeholder level including economic, social, and environmental methods that can be employed at local, regional or national scale and which are typically employed to inform policy and decision making regarding ORE. Governance sets the stage within which management occurs. Wider impacts to the firm undertaking the project will take into account "externalities" of the project across the three fields. In this model, key methods identified are mapped onto this parameter space and the connectivity explored. The paper demonstrates that the three pillars are inter-connected and each must be considered in any meaningful assessment of ORE sustainability. An integrated assessment approach has the ability to address both the private and the public aspects of an ORE development, This analysis provides insights on existing best practice, but also reveals the potential for disconnect between an ORE project's commercial viability and its contribution to environmental and social goals.